Effect of Brain Based Learning on Students Biology Learning Outcomes - Ermita Putri; Jamaluddin Jamaluddin; I Wayan Merta (Jurnal Pijar MIPA, 2026)
Low biology learning outcomes are often linked to conventional teacher-centered instruction, which limits student engagement and active participation. This study was conducted to address these challenges by examining the effect of Brain-Based Learning on students’ biology achievement. The main objective was to determine whether this innovative approach could significantly improve learning outcomes compared to traditional methods. A quasi-experimental design was employed, specifically the pretest-posttest control-group design. The sample was selected using purposive sampling, resulting in two classes: an experimental class that received Brain-Based Learning treatment and a control class that continued with conventional instruction. Data collection techniques included biology achievement tests administered before and after the intervention, complemented by classroom observations to monitor the implementation process and student involvement. Data analysis was carried out using an independent sample t-test to assess the significance of differences between the two groups. The results revealed a clear and significant effect of Brain-Based Learning on students’ biology learning outcomes, as indicated by a p-value of 0.000, which is below the 0.05 threshold. The average post-test score in the experimental class was 78.45, while the control class scored only 49.32. These findings demonstrate that Brain-Based Learning is more effective than conventional methods in enhancing students’ understanding of biological concepts. In conclusion, Brain-Based Learning significantly improves biology learning outcomes and fosters more active, meaningful, and engaging learning experiences. The practical implication of this study is that teachers should consider adopting Brain-Based Learning as an innovative instructional strategy to enhance the quality of biology education. By shifting from teacher-centered to student-centered approaches, educators can create learning environments that better support achievement and long-term retention of scientific knowledge.